ANALISIS KECEPATAN GELOMBANG GESER (Vs) MENGGUNAKAN MULTICHANNEL ANALYSIS OF SURFACE WAVE (MASW) DI KECAMATAN JAMBI LUAR KOTA - Musyarofah, Leni Nurli; Resta, Ichy Lucya; MZ, Nasri (Jurnal Meteorologi dan Geofisika, 2024)
Jambi Luar Kota is one of the sub-districts with an increasing population density and development level. It can be seen in the last 10 years (2010-2020), 39 populations/km2 with a total population of 62,687 people. The increase in population density impacts infrastructure development, which also increases. The site class maps need to be considered for infrastructure development by considering the development rules in accordance with SNI 1726:2019. This study used the Multichannel Analysis of Surface Wave (MASW) method, which measures variations in surface wave velocity with 21 lines. The average value of the shear wave velocity at a depth of 30 m MASW measurements ranged from 153.24 m/s - 420.86 m/s, consisting of SC site class, SD site class, and SE site class.  SC site class with a Vs30 value of 358.88 m/s-420.86 m/s was found on the east side of the middle part of the Jambi Luar Kota Sub-district. Meanwhile, the SD site classes are evenly distributed in the Jambi luar Kota Sub-district.  The SE site class is located on the north and east sides of the Jambi Luar Kota Sub-district with a Vs30 value of 153.24 m/s, which in this case is supported by geotechnical data in the form of water content (w) (43.03%), plasticity index (PI) (23.26) and a shear strength test of 17,652 kPa.  The area with a low Vs30 value (<175 m/s) is an area that has the potential to get relatively more significant shocks when ground movement occurs.